Management of Aesthetic Crown Lengthening After Orthodontic Treatment: A 6 Month Evaluation Case Report - Hidayat, Dodo; Lastianny, Sri Pramestri (Interdental Jurnal Kedokteran Gigi (IJKG), 2024)
Introduction: Three interrelated elements are responsible for creating an ideal smile: teeth, gingiva, and lips. The current concept of aesthetics focuses not only on the teeth but on the gingiva as well, thus make these two elements important and related to one another. Maintaining the healthy condition of periodontal tissue around the teeth is vital for functional and aesthetic aspects. Crown lengthening is a surgical procedure to increase the length of clinical crowns to achieve an ideal crown to gingival ratio with or without bone reduction. Crown lengthening procedures require a good understanding of biological width and how to achieve it. This case report aims to demonstrate the success of crown lengthening with ostectomy for the treatment of excessive gingival display in post orthodontic treatment patients. Case: A 25-year-old female patient came to the periodontic clinic on referral from an orthodontic, for correction of a disproportionate dental condition after braces treatment was completed. Treatment: Clinical examination showed disproportionate length and width of crowns due to excessive gingival display and gingival enlargement in the region of teeth 33 to 43. Case Management: In this case report, crown lengthening treatment was performed from teeth 13 to 23 with open flap for ostectomy and flap was restored with sling suture, contact point repair on teeth 12 and 22, and gingivectomy on mandibular anterior teeth. Conclusion: Aesthetic crown lengthening surgery results in a high satisfaction level of the patient and predictable and stable results.